The Role of Digital Marketing and ICT in Enhancing Regional Economic Growth: Evidence from East Java - Dina Utari; Danang Sofa Ma’arif; Akbar Mulia Ramadhan; Novita, Yeyen (Disclosure: Journal of Accounting and Finance, 2025)
This study aims to analyze the role of digital productivity in driving economic growth in East Java Province during the period 2015–2024. The growth of information and communication technology (ICT) has made a significant contribution to the acceleration of the economy in the digital era, especially through the development of e-commerce and technology-based businesses. This study uses a mixed method, namely qualitative analysis with a netnography approach using NVivo software on netizens' comments on marketing themed YouTube content, as well as quantitative analysis with panel data from 38 districts/cities in East Java analyzed using EViews. The results of the qualitative analysis revealed that digital marketing strategies and technology adaptation are the main factors in increasing business productivity. Meanwhile, the results of the quantitative analysis show that the ICT development index, the number of workers, and the GDP significantly affect economic growth in East Java. These findings confirm that digital productivity is key to supporting sustainable economic growth in the modern era.